Calcium Oxalate Differentiates Human Monocytes Into Inflammatory M1 Macrophages - Dominguez-Gutierrez, Paul R.; Kusmartsev, Sergei; Canales, Benjamin K.; Khan, Saeed R. (Frontiers in Immunology, 2018)
Purpose: A number of hyperoxaluric states have been associated with calcium oxalate (CaOx) deposits in the kidneys. In animal models of stone disease, these crystals interact with circulating monocytes that have migrated into the kidney as part of innate immunity. Similarly, macrophages surround CaOx crystals in kidneys of patients excreting high levels of oxalate. We investigate the effect of this exposure and subsequent human immunological response in vitro. Materials and Methods: Primary human monocytes were collected from healthy donors and exposed to CaOx, potassium oxalate, and zinc oxalate. Cytokine production was measured with a multiplex ELISA. Quantitative reverse transcription-polymerase chain reaction was done to validate the mRNA profile expression. M1 macrophage phenotype was confirmed with immunofluorescence microscopy. Results: Both primary monocytes and THP-1 cells, a human monocytic cell line, respond strongly to CaOx crystals in a dose-dependent manner producing TNF-α, IL-1β, IL-8, and IL-10 transcripts. Exposure to CaOx followed by 1h with LPS had an additive effect for cytokine production compared to LPS alone, however, LPS followed by CaOx led to significant decrease in cytokine production. Supernatants taken from monocytes that were previously exposed to CaOx crystals enhance M2 macrophage crystal phagocytosis. CaOx, but not potassium or zinc oxalate, promotes monocyte differentiation into inflammatory M1-like macrophages. Conclusions: In our in vitro experiment, human monocytes were activated by CaOx and produced inflammatory cytokines. Monocytes recognized CaOx crystals through a specific mechanism that can enhance or decrease the innate immune response to LPS. CaOx promoted M1 macrophage development. These results suggest that monocytes have an important role promoting CaOx-induced inflammation.